Pengaruh Penggunaan Getah Pepaya (Carica Papaya L.) Pada Proses Dekafeinasi Terhadap Penurunan Kadar Kafein Kopi Robusta - Pangan, Media (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 4 No 2 (2017): Scientific Journal of Food Technology, 2021)
Decafeination is a process for reduction of caffeine content in coffee beans. This study is aimed to find the effects of use of papaya’s sap (Carica papaya L) to the reduction of caffeine content of robusta coffee and find the concentration of papaya’s sap (Carica papaya L.) that should be used to produce decaffeinated coffee according to the requirements. This study uses a Completely Randomized Design (CRD); by using five levels of papaya’s sap concentration; at 0%, 1.5%, 3%, 4.5% and 6%, with 3 repetition so obtained 15 experimental units. The results of the study showed that the use of papaya’s sap affects the reduction of caffeine content in robusta coffee. At a concentration of 6% addition of papaya’s sap decaffeinated coffee produce according to the requirements that the caffeine content of 0.24% by 11.34% moisture content, 0.07% ash content, and 9.72% protein content.